Multiple Antimicrobial Resistance in Plague: An Emerging Public Health Risk - Welch, Timothy J.; Fricke, W. Florian; McDermott, Patrick F.; White, David G.; Rosso, Marie-Laure; Rasko, David A.; Mammel, Mark K.; Eppinger, Mark; Rosovitz, M.J.; Wagner, David; Rahalison, Lila; LeClerc, J. Eugene; et al. (PLOS ONE, 2007)
Antimicrobial resistance in Yersinia pestis is rare, yet constitutes a significant international public health and biodefense threat. In 1995, the first multidrug resistant (MDR) isolate of Y. pestis (strain IP275) was identified, and was shown to contain a self-transmissible plasmid (pIP1202) that conferred resistance to many of the antimicrobials recommended for plague treatment and prophylaxis. Comparative analysis of the DNA sequence of Y. pestis plasmid pIP1202 revealed a near identical IncA/C plasmid backbone that is shared by MDR plasmids isolated from Salmonella enterica serotype Newport SL254 and the fish pathogen Yersinia ruckeri YR71. The high degree of sequence identity and gene synteny between the plasmid backbones suggests recent acquisition of these plasmids from a common ancestor. In addition, the Y. pestis pIP1202-like plasmid backbone was detected in numerous MDR enterobacterial pathogens isolated from retail meat samples collected between 2002 and 2005 in the United States. Plasmid-positive strains were isolated from beef, chicken, turkey and pork, and were found in samples from the following states: California, Colorado, Connecticut, Georgia, Maryland, Minnesota, New Mexico, New York and Oregon. Our studies reveal that this common plasmid backbone is broadly disseminated among MDR zoonotic pathogens associated with agriculture. This reservoir of mobile resistance determinants has the potential to disseminate to Y. pestis and other human and zoonotic bacterial pathogens and therefore represents a significant public health concern.